1973
DOI: 10.1055/s-0028-1098214
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Gastritis in the Upper Portion of Stomach by Endoscopic Congo Red Test

Abstract: Technique for endoscopic examination of the extent of gastritis in upper portion of the stomach was established with congo red solution. Gastritis in upper portion of the stomach was then examined by this technique and in resected stomachs. The results was as follows: 1. By means of congo red test, it is possible to demonstrate the extent of gastritis in the upper stomach as "non-discolored area" characterized by absence of acid secretion.2. Histological characteristics of gastritis in the upper stomach consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 2 publications
4
25
0
Order By: Relevance
“…Pos sibly, the reason why these cancers are so rare in Japan is related to the extent of the cardiac gland area. As previously reported [12,13], the cardiac gland area is very narrow, if present at all. In 11 (29.7%) out of 37 patients examined, we were unable to detect any car diac glands, and in other patients, the mean width of the cardiac gland area was only 2.2 mm (0.5-9 mm).…”
Section: Discussionsupporting
confidence: 55%
“…Pos sibly, the reason why these cancers are so rare in Japan is related to the extent of the cardiac gland area. As previously reported [12,13], the cardiac gland area is very narrow, if present at all. In 11 (29.7%) out of 37 patients examined, we were unable to detect any car diac glands, and in other patients, the mean width of the cardiac gland area was only 2.2 mm (0.5-9 mm).…”
Section: Discussionsupporting
confidence: 55%
“…Bockus [8] stated that the size of the cardiac gland area was 0.5-3.0 cm, and Netter [17] stated that the size was 0.5-4.0 cm. Furthermore, Tatsuta [24] described the size as being 2 cm in average, ranging from 1.0 to 5.7 cm. Kato et al [13] also reported the cardiac gland area as being 1 cm in size at most.…”
Section: Discussionmentioning
confidence: 99%
“…HP-related chronic gastritis usually starts in the antrum and expands proximally towards the body of the stomach (Kimura, 1972;Tatsuta et al, 1973). As several studies dealing with endoscopic biopsies or chromoendoscopic testing have found that progression of chronic atrophic gastritis (CAG) increases the risk of cancer (Meister et al, 1979;Sipponen et al, 1985;Siurala et al, 1966;Tatsuta et al, 1993;Testoni et al, 1987), accurate and reliable evaluation of the extent of CAG is considered important for identifying individuals at high risk of cancer.…”
Section: Serum Pg Testmentioning
confidence: 99%